UPFRONT NEPHRECTOMY VERSUS PREOPERATIVE CHEMOTHERAPY IN WILM’S TUMOUR - Manzoor, Ruqayya; Yasmeen, Nuzhat (Journal of Ayub Medical College Abbottabad, 2019)
Background: Wilms tumour is the most common renal tumour in paediatric age group. This study was done to compare the two approaches used for treatment, namely upfront nephrectomy versus pre-operative chemotherapy. Methods; A descriptive cross-sectional study was done enrolling all the patients of Wilms tumour reporting to Oncology unit Children’s Hospital during the study period. A total of 80 patients were divided into 2 groups. One group (n=40) had upfront surgery while the other (n=40) received pre-op chemotherapy before surgery. Both groups were compared for outcomes including whether treatment completed and declared cured, lost during treatment against medical advice, or died during treatment. Results; It was found that stage 2 patients were more likely to get upfront surgery done while stage 3,4 and 5 were likely to get pre-operative chemotherapy before nephrectomy. Also, favourable histology was associated with better outcome overall outcome. Keywords: Wilms tumour; Nephrectomy; Chemotherapy; Preoperative Chemotherapy